Avaliação nutricional da silagem biológica de resíduos de pescado na alimentação de alevinos de tilápia - Souza, Joana Maria Leite de (1998)
Fish silage was obtained through the enzymatic hydrolysis of ground fish promoted by a vegetable based biological ferment. Acidity, pH, chemical composition, gross energy and organoleptic characteristics of the were determined. The following silage levels were adopted: 0, 10, 20 and 30 5 was incorporated into the diet of Tilapia alevins (Oreochromis niloticus)as the main protein source in the experimental treatmemt (T2, T3 and T4, respectvely), and its effect on growth was compar with a control treatment (T1). The control included a combination of bovine (meat and bone) meal and fish as the experimental and treatment were isoproteic and isocaloric balanced. Both treatment consisted of twelve round concret tanks holding na average of 8 fish each (mean fish weight were 3,0 + 0,4g and 4.1 + 0,2 g respectively). The alevins were welghed and mesured every 15 days and twice per day (ca. 7% the fish biomass of each tank) over the 97 day experient.